Systematic studies of the Philippine cheyletid mites (Acarina). V. New species and new records with a note on the synonymy of Tutacheyla corpuz-raros - Corpuz-Raroz, L.A (1988)
Four new species of cheyletids are described and illustrated from the Philippines, namely, Acaropsellina filipina, ?Eucheyletia nindota, Hemicheyletia athenae, and H. leytensis. Cheyletophyes apicola Fain, Lukoschus and Nadchatram, Hypopicheyla mirabilis Volgin, Lepidocheyla gracilis Volgin and Neoeucheyla loricata (Berlese) are reported for the first time from the country. New locality and habitat records are also given for four species described earlier from Luzon. Indonesiacheyla Thewke, 1980 is regarded as junior synonym of Tutacheyla Corpuz-Raros, 1972. A key to the two known species of Tutacheyla is given.